1986
DOI: 10.1007/bf00614519
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of the electroreceptive midbrain in an elasmobranch (Platyrhinoidis triseriata)

Abstract: The response properties of 322 single units in the electroreceptive midbrain (lateral mesencephalic nucleus, LMN) of the thornback ray, Platyrhinoidis triseriata, were studied using uniform and local electric fields. Tactile, visual, or auditory stimuli were also presented to test for multimodality. Most LMN electrosensory units (81%) are silent in the absence of stimulation. Those with spontaneous activity fired irregularly at 0.5 to 5 impulses/s, the lower values being more common. Two units had firing rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…This projection was also reported by Luiten [1981b], Bodznick and Northcutt [1984], and Fiebig and Bleckmann [1989]. It might be part of an ascending electrosensory pathway [Schweitzer, 1983[Schweitzer, , 1986Bodznick and Northcutt, 1984]. In our study, only a few cells were labeled in those dorsal thalamic areas that may correspond to the lateral geniculate and ventral optic nucleus of Luiten [1981b].…”
Section: The Dorsomedial Palliummentioning
confidence: 51%
“…This projection was also reported by Luiten [1981b], Bodznick and Northcutt [1984], and Fiebig and Bleckmann [1989]. It might be part of an ascending electrosensory pathway [Schweitzer, 1983[Schweitzer, , 1986Bodznick and Northcutt, 1984]. In our study, only a few cells were labeled in those dorsal thalamic areas that may correspond to the lateral geniculate and ventral optic nucleus of Luiten [1981b].…”
Section: The Dorsomedial Palliummentioning
confidence: 51%
“…Boord and Northcutt [1982] were unable to trace secondary lateral line projections to it but showed that it receives electrosensory afferents from the more caudally situ ated lateral subdivision [Boord and Northcutt, 1983]. Schweitzer [ 1986], using electrophysiological methods in the thornback guitar fish, presents evidence that the anterior and lateral subdivisions represent a single somatotopic map of the electrosensory body surface and suggests that they are parts of the same nucleus. Bleckmann et al [1987] recorded responses to both electrical and mechanical stimuli from cells of the an terior nucleus in the thornback guitar fish and do not believe that it is a rostral extension of the lateral nuc leus.…”
Section: Discussionmentioning
confidence: 99%
“…The transverse sections are shown from behind, so that a left-side lesion is seen on the left side of the sections and vice versa. h DCBA demonstrated a topological correlation between stim ulus direction and neural processing in the midbrain of anamniotes in hearing [Pettigrew et al, 1978[Pettigrew et al, , 1981, the somatosensory system [Comer and Grobstein, 1981b], electroreception [Scheich and Maler, 1976;Knudsen, 1977Knudsen, , 1978Bastian, 1982;Schweitzer, 1986], and the mechanoreceptive lateral line [Knud sen, 1977;Zittlau et al, 1986]. Behavioral validation for the functional significance of these results, how ever, is lacking.…”
Section: Introductionmentioning
confidence: 99%